Uniform pressing mechanism in large-area roll-to-roll nanoimprint lithography process - Kim, Ga Eul; Kim, Hyuntae; Woo, Kyoohee; Kang, Yousung; Lee, Seung Hyun; Jeon, Yongho; Lee, Moon G.; Kwon, Sin (Applied Sciences (Switzerland), 2021)
We aimed to increase the processing area of the roll-to-roll (R2R) nanoimprint lithography (NIL) process for high productivity, using a long roller. It is common for a long roller to have bending deformation, geometric errors and misalignment. This causes the non-uniformity of contact pressure between the rollers, which leads to defects such as non-uniform patterning. The non-uniformity of the contact pressure of the conventional R2R NIL system was investigated through finite element (FE) analysis and experiments in the conventional system. To solve the problem, a new large-area R2R NIL uniform pressing system with five multi-backup rollers was proposed and manufactured instead of the conventional system. As a preliminary experiment, the possibility of uniform contact pressure was confirmed by using only the pressure at both ends and one backup roller in the center. A more even contact pressure was achieved by using all five backup rollers and applying an appropriate pushing force to each backup roller. Machine learning techniques were applied to find the optimal combination of the pushing forces. In the conventional pressing process, it was confirmed that pressure deviation of the contact area occurred at a level of 44%; when the improved system was applied, pressure deviation dropped to 5%.
Keywords: Contact pressure; High productivity; Nanoimprint lithography; Roll-to-roll process; Roller bending